Importância do ambiente (ar e superfície) e das mãos de profissionais de saúde na epidemiologia de pneumonia associada à ventilação mecânica por Staphylococcus aureus em unidade de terapia intensiva de adultos - Rocha, Lílian Alves (2012)
Staphylococcus aureus is one of the most common pathogens in the cause of ventilator-associated pneumonia (VAP) and nasal colonization is the major risk factor for subsequent development of infection by this organism. The aim of this study was to analyze the epidemiology of VAP by S. aureus resistant (MRSA) or sensitive (MSSA) to methicillin in patients admitted to the adult Intensive Care Unit of Hospital de Clinicas of Federal University of Uberlandia in the period between September 2008 and August 2010. The VAPs were defined based on clinical and radiological criteria and microbiological count106UFC/mL in tracheal aspirate, and risk factors for MRSA colonization were determined from a study case versus control. The identification of S. aureus was performed by conventional microbiological tests, and the antimicrobial susceptibility profile was determined by a disk diffusion technique. The mecA gene was characterized by the technique of polymerase chain reaction (PCR) and clonal profile by pulsed-field gel electrophoresis (PFGE). Additionally, 85% (873 of 1037) of the patients admitted were evaluated for nasal colonization and isolates of the environment (air and surface), and the hands of health care personal were also isolated for analysis. In total, 475 mechanically ventilated patients were analyzed and of these 21 (4.4%) progressed to VAP by S. aureus. The incidence rates of VAP and VAP by S. aureus per 1000 patients/day were 15.6 and 1.9, respectively. The MRSA phenotype represented only 19% of the etiology of VAPs S. aureus, and all these were considered late. Among the patients investigated for nasal colonization, the frequency of S. aureus was 26.7%, with an incidence of the 21.6 per 1000 patients/day. The colonization was associated with an increased incidence of VAP by this microorganism in accordance with Pearson\'s correlation. The nasal colonization was statistically significant risk factor for the development of this infection regardless of phenotype. Although several risk factors were identified for MRSA colonization in univariate analysis, such as antibiotics, colonization time, admission diagnosis, and invasive procedures, only the use of tracheostomy was independently associated. The environmental contamination of surfaces with S. aureus was detected near the beds of patients infected or colonized at a frequency of 10.7%, showing a positive correlation. A similar frequency (8.2%) was also observed in the hands of health care personal. The temporal/spatial relationship was observed in about half (47.6%) of the patients with S. aureus. The results showed the presence of a variety of genotypes in the unit; of the 28 samples tested, 13 PFGE profile were found, 6 corresponded to MSSA, and 7 to MRSA. The same clonal profile was observed in samples corresponding to the same patient including colonization, infection, environment, and the hands of health care professionals. The incidence of PAVs S. aureus was low with a predominance of cases by MSSA and nasal colonization represented a risk factor for VAP evolution. There was participation of the environment as a reservoir secondary to MRSA infection and there was evidence of cross-transmission in unit.